Aplikasi Perpustakaan SMK NU Al Hidayah Berbasis Website - Putri Noviati, Wanda; Nurkhafidhoh, Nurkhafidhoh (Green Publisher Indonesia, 2025)
Libraries have an important role in supporting the learning process in educational institutions, but manual management often causes inefficiencies in recording borrowing and returning books. This research aims to design and develop a web-based library system to improve the effectiveness of library management at SMK NU Al Hidayah Ngimbang. The research method used is the Waterfall system development model, which includes the stage of needs analysis, design, implementation, testing, and system maintenance. System testing is carried out using the Black Box Testing method to ensure that the functionality of the application runs properly. The results of the study show that this web-based library system can make it easier for admin staff to manage book borrowing and return data more accurately and efficiently. In addition, this application also makes it easy for students to access book catalogs and apply for loans online. The implementation of this system has succeeded in reducing the risk of data loss due to manual recording and increasing efficiency in library management. In conclusion, the implementation of a web-based library system is able to optimize library services by providing faster and more accurate access to information for users